2012
DOI: 10.5539/ijps.v4n2p228
|View full text |Cite
|
Sign up to set email alerts
|

Abstinence from Premarital Sex: A Precursor to Quality Relationship and Marital Stability in Subsequent Marriage in Nigerian Society

Abstract: The last half of the 20th century has witnessed substantial changes in the practice of premarital partnership among the youths and unmarried adults. The growing trend in premarital behavioural pattern of today exposes teenagers to living in the world of great sexual exploration and indulgence. This could negatively impact future marital quality and marital stability. This study examined the influence of premarital sex among 3,824 married people where 1931 (50.5%) were males and 1893 (49.5%) were female. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
(14 reference statements)
1
10
0
Order By: Relevance
“…This finding is in line with Okafor (2014) [17] findings which revealed that morality training had a positive effect on the maladjustment behaviour of the students. In consonance, Ogunsola (2011) [15] advocated for necessary empowerment of the youngsters, especially the female teenagers, through proper sex education to avoid the harmful consequences of premarital behaviours that often lead to sexual activities. It is an essential step taken to properly inform the young adults about the obstructive outcome of premarital behaviours such as romantic intimacy and sexual relationships to avoid its negative consequences in their future marriages, hence the usefulness of morality training.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in line with Okafor (2014) [17] findings which revealed that morality training had a positive effect on the maladjustment behaviour of the students. In consonance, Ogunsola (2011) [15] advocated for necessary empowerment of the youngsters, especially the female teenagers, through proper sex education to avoid the harmful consequences of premarital behaviours that often lead to sexual activities. It is an essential step taken to properly inform the young adults about the obstructive outcome of premarital behaviours such as romantic intimacy and sexual relationships to avoid its negative consequences in their future marriages, hence the usefulness of morality training.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Empirically, Okafor (2014) [17] revealed that morality training had a positive effect on the maladjustment behaviour of the students. In consonance, Ogunsola (2011) [15] advocated for necessary empowerment of the youngsters, especially the female teenager, through proper sex education to avoid the harmful consequences of premarital behaviours that often lead to sexual activities. Igba, Ofem and Isu (2016) [5] who revealed that good guidance and counselling are good strategies for restoring morality among youths within families.…”
Section: Effect Of Morality Training Technique On Cohabitation Behavi...mentioning
confidence: 99%
“…Cohabitation resulted in very likely experiences of abuse, exploitation, intimate partner violence, murder, and suicide (19)(20)(21). Due to the frequent lack of commitment and transient nature of the relationship, cohabiting female youths are frequently at risk for poor mental health following disagreements (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, sexual abstinence before marriage is suggested as the best protective method for sexually transmitted diseases and their outcomes ( 4 , 5 ). In addition there is evidence that adolescents who engage in premarital sexual activities may not experience the same quality marital relationship and stability as that of married people who abstained from premarital sexual activities ( 6 ). Thus, sexual abstinence has been recommended to prevent young adolescents from adverse outcomes of premarital sexual behaviors ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%